2013
DOI: 10.1371/journal.pone.0075812
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydroxybutyrate Targets Mammalian Mitochondria and Increases Permeability of Plasmalemmal and Mitochondrial Membranes

Abstract: Poly(3-hydroxybutyrate) (PHB) is a polyester of 3-hydroxybutyric acid (HB) that is ubiquitously present in all organisms. In higher eukaryotes PHB is found in the length of 10 to 100 HB units and can be present in free form as well as in association with proteins and inorganic polyphosphate. It has been proposed that PHB can mediate ion transport across lipid bilayer membranes. We investigated the ability of PHB to interact with living cells and isolated mitochondria and the effects of these interactions on me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Recent reports have also confirmed increased propensity toward PT caused by the presence of polyphosphates, chains of 10s to 100 s of repeating phosphates linked by ATP-like high energy bonds (Abramov et al, 2007; Seidlmayer et al, 2012; Holmstrom et al, 2013; Stotz et al, 2014). The actions of Ca 2+ may also require polyhydroxybutyrate (PHB), which enters mitochondria and enhances the ability of Ca 2+ to induce PT (Elustondo et al, 2013). Although the above conditions occur under pathological circumstances, evidence for physiological opening of the mPTP has been described including flickering short of permanent opening (Hausenloy et al, 2004; Crompton, 1999; Huser & Blatter, 1999; Korge et al, 2011; Petronilli et al, 1999; Wang et al, 2008; Ichas & Mazat, 1998; Jouaville et al, 1998).…”
Section: Physiological and Metabolic Role Of The Permeability Transitmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent reports have also confirmed increased propensity toward PT caused by the presence of polyphosphates, chains of 10s to 100 s of repeating phosphates linked by ATP-like high energy bonds (Abramov et al, 2007; Seidlmayer et al, 2012; Holmstrom et al, 2013; Stotz et al, 2014). The actions of Ca 2+ may also require polyhydroxybutyrate (PHB), which enters mitochondria and enhances the ability of Ca 2+ to induce PT (Elustondo et al, 2013). Although the above conditions occur under pathological circumstances, evidence for physiological opening of the mPTP has been described including flickering short of permanent opening (Hausenloy et al, 2004; Crompton, 1999; Huser & Blatter, 1999; Korge et al, 2011; Petronilli et al, 1999; Wang et al, 2008; Ichas & Mazat, 1998; Jouaville et al, 1998).…”
Section: Physiological and Metabolic Role Of The Permeability Transitmentioning
confidence: 99%
“…When viewed from the inter-membrane space, the denuded c-subunit oligomer appears to have a central pore-like structure that is normally obscured by the F 1 stalk components, suggesting that the mouth of the pore may be unmasked by removal of F 1 (Pogoryelov et al, 2007). Although it has been suggested that phospholipids occupy the central cavity of the c-subunit ring in F 1 F O ATP synthases from different species (Oberfeld et al, 2006; Meier et al, 2001; Matthies et al, 2009) other evidence provides for formation of a proteolipid or proteophospholipid channel structure within the central lipid region upon activation of PT (Abramov et al, 2007; Elustondo et al, 2013; Azarashvili et al, 2014; McGeoch & McGeoch, 2008; Pavlov et al, 2005). Polyhydroxybutyrate (PHB) is a polymer distinct from the lipids that may form an ion channel within the lipid milieu if mammalian c-subunit is indeed filled with PHB (Elustondo et al, 2013; Pavlov et al, 2005).…”
Section: Structural Location Of the Pore Within The C-subunit Ringmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have also confirmed increased activity of PT by polyphosphates, chains of 10s to 100s of repeating phosphates linked by ATP-like high energy bonds [5861]. The actions of Ca 2+ may also require polyhydroxybutyrate (PHB), which enters mitochondria and enhances the ability of Ca 2+ to induce PT [62]. …”
Section: Regulation Of the Permeability Transition Porementioning
confidence: 99%
“…When viewed from the inter-membrane space, the denuded c-subunit oligomer appears as a ring with a central pore-like structure that is normally obscured by the F 1 stalk components gamma, delta and epsilon, suggesting that the pore may form within the center of the ring given the proper hydrophilic conformation [129]. Although it has been suggested that phosphlipids occupy the central cavity of the c-subunit ring in F 1 F O ATP synthases from different species [156158] other evidence provides for formation of a proteolipid or proteophospholipid channel structure within the central lipid region [58,62,118,131,159]. Data suggest a working model whereby the c-subunit pore forms within the proteolipid milieu upon activation of mPTP (for example by elevated matrix Ca 2+ ) whereupon the ring expands and F 1 shifts; the pore is closed by a decrease in diameter of the ring and inactivated by binding of the F 1 components to the ring (Figs.…”
Section: The Mptp a Molecular Definitionmentioning
confidence: 99%